Evaluation of polymorphism at Cod on 192 of Paraoxonase 1 on its kinetic behavior - Poh, R.; Muniandy, S. (2009)
Human paraoxonase 1 (PON1), a High-Density Lipoprotein (HDL)-associated esterase has been implicated in slowing down the development of atherosclerosis. In the present study, kinetic and inhibition studies on PON1 were conducted to assess three parameters: the Michaelis constant (KM) and maximal rate of metabolisme (Vmax) of paraoxonase and inhibition constant (Ki) of phenylacetate. Human paraoxonase 1 (PON1) activity was measured spectrophotometrically at 405 nm, using plasma samples in basal (without added NaCl) and salt-stimulated assays with 1 M NaCl. Inhibition studies were performed using phenylacetate as an inhibitor of PON1 in basal assays, pH 8.0. Estimates of KM and Vmax were obtained from the Lineweaver-Burk plot. Estimates of Ki were obtained from the secondary plot of apparent KM (KM,app) versus inhibitor concentration. The parameter values were evaluated for the genotypes PON1192QQ, -QR, -RR. In salt-stimulated assays, the Vmax increased two-fold for the PON1192QQ samples and three to five-fold for the PON1192RR samples compared with basal assays. Similarly, it increased four-fold for PON1192QR samples. Michaelis constant (KM) was comparable with or without 1.0 M NaCl across the three genotypes. The Lineweaver-Burk and Dixon plots revealed that phenylacetate was a predominantly competitive inhibitor exhibiting linear mixed type inhibition. The Ki values were also comparable across the three genotypes. We conclude that the three kinetic parameters of PON1 in the Malaysian population estimated in the present report were comparable with those reported by other studies on PON1 from Caucasian populations.